Implementing noninvasive follicular thyroid neoplasm with papillary‐like nuclear features may potentially impact the risk of malignancy for thyroid nodules categorized as AUS/FLUS and FN/SFN. Issue 2 (30th November 2017) - Li, Weihong; Sciallis, Andrew; Lew, Madelyn; Pang, Judy; Jing, Xin
Abstract : Background: Noninvasive encapsulated follicular variant of papillary thyroid carcinoma (PTC) has recently been reclassified as noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP). Implementation of the new terminology may alter the implied risk of malignancy (ROM) across the six categories of The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC). Methods: The study cohort consisted of thyroid fine needle aspiration (FNA) cases which were assessed between January 2011 and June 2016 and led to surgical resections. For each case, patient demographics as well as cytologic and corresponding histologic diagnoses were recorded. The surgical specimens diagnosed as follicular variant of PTC (FVPTC) were re‐reviewed to identify cases that met the diagnostic criteria for NIFTP. The ROM with and without exclusion of NIFTP from malignant categorization, as well as the relative change in ROM were calculated for individual categories of TBSRTC. Results: A total of 908 FNA cases with surgical follow‐up were retrieved and PTC was identified in 252 (27.8%) surgical specimens. Twenty‐nine of 252 (11.5%) were initially classified as FVPTC, of which 17 (6.7%) were reclassified as NIFTP. The cytologic interpretations for the majority of NIFTP cases were atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS, n  = 8) or follicular neoplasm/suspicious for neoplasm/(FN/SFN, n  = 4). Excluding NIFTP from malignant categorization resulted in a relative decrease in ROM in AUS/FLUS (25.8%) and FN/SFN (22.3%) categories. Conclusion: Our institutional data demonstrates that eliminating NIFTP from malignant categorization may result in a reduction of the implied ROM for AUS/FLUS and FN/SFN categories.